Radiologic features of primary intracranial ectopic germinomas: Case reports and literature review. Issue 52 (December 2016) - Wei, Xin-Hua; Shen, Hui-Cong; Tang, Shou-Xian; Gao, Cui-Hua; Ren, Ji-Liang; Ai, Lin; Dai, Jian-Ping
Abstract: Rationale: Germinomas are sensitive to radiation therapy and chemotherapy; therefore, correct imaging diagnosis is crucial for them. However, the imaging findings of germinomas originating from off-midline regions displayed different patterns from those originating from midline areas. Patient concerns: The objective of this study is to describe the radiologic features of primary ectopic germinoma. We reviewed the MR and CT findings of 12 patients with histologically proven off-midline ectopic germinomas with off-midline locations. Interventions: All of these patients underwent conventional MR images and 3 of them underwent diffusion images. Additional CT images were available in 3 patients. Analysis was focused on the shape and entity of tumors in images, signs of hemiatrophy, and the involvement of fibers in diffusion images. Outcomes: Well-defined (8/12) and ill-defined margin masses (4/12) were identified according to the shape of the mass. Multicystic masses were seen in 11 of the 12 patients. The solid component of the tumors had a high density (3/3) with calcifications (2/3) on CT images, iso- to hypointensity in T2WI (11/12) and restricted diffusion on apparent diffusion coefficient (ADC) maps (3/3). Hemiatrophy was observed in 5 cases and progressive hemiatrophy was observed in 1 case. Other signs included mild peritumoral edema (10/12), and hydrocephalus (7/12). Additionally, infiltration of the corticospinal tract (CST) was identified on diffusion tensor imaging (DTI) (2/2). Lessons: The results indicate that multicysitic entities and hypointensities in solid components on T2WI and hemiatrophy are the imaging features of ectopic germinomas. DTI has potential for assessing CST involvement.